IMPLEMENTATION OF RISK MANAGEMENT SYSTEM IN CASE OF DEVELOPMENT OF LEASING CONTRACTS IN THE CONDITIONS OF THE STATE REFORMING OF AN INDUSTRY - O. Larina (Publishing House of the State University of Management, 2017)
In article the importance and need of implementation of risk management system in the course of forming of leasing contracts are proved. The most urgent the matter became in connection with the reform of a leasing industry initiated by state bodies of the power. The Bank of Russia and the Ministry of Finance plan implementation of risk management in leasing companies as obligatory element of general structure. Thus, the corresponding scheme with the description of stages of a risk management of the leasing organization is constituted, and its importance for the organizations in the course of the state reform of a leasing industry is also provided.